Tradisi Tolak Bala di Desa Ranto Natas Kecamatan Panyabungan Timur Kabupaten Mandailing Natal - Muhammad Ridwan; Yenni Rahman; Efizal A; Irpan Rambe (Kampus Akademik Publiser, 2026)
The background of this issue is to discuss the tradition of tolak bala in the Ranto Natas community, East Panyabungan District, Mandailing Natal Regency. The main issues in this paper are: the history and basis of the tolak bala tradition, and how the tolak bala tradition is carried out. The purpose of this study is to reveal the history and basis of the tolak bala tradition, and to reveal how the tolak bala tradition is carried out. In this study, the author used field research with a descriptive qualitative research method to describe the tolak bala activities by conducting observations, interviews, and documentation, then analyzing and reducing the data obtained. The author found that there was a study of the Living Qur'an in the implementation of the tolak bala tradition. The results of this study can be summarized as follows. First, before the Tolak Bala was held, there had been pests on the community's crops. Second, there had been severe flooding. After these events, the religious scholar Mr. Ali Mukhtar and community leaders in the village held a meeting to decide to hold a recitation of the Yasin every Monday night. With the hope that the recitation of Yasin would protect the village and keep it safe from calamities and disturbances. Third, landslides. That is why the tradition of warding off evil by reciting Yasin is still practiced regularly every Monday night.